Prediction of the Digital Game Rating Systems based on the ESRB - Ahmad Qasim AlHamad, Khaled Mohammad Alomari,; Mbaidin, Hisham o.; Salloum, Said (Opción, 2019)
This study tries to find out the best model for prediction video game rate categories. A representation from four rating categories (everyone, everyone 10+, teen, mature) was used for the analysis. The paper follows CRISP-DM approach under Rapid Miner software to business and data understanding, Data preparation, model building and evaluation. The researchers compared prediction among six model and the results showed that the Generalized Linear Models (GLMs) achieved a best accuracy (0.9027), also results highlighted eight important content descriptions to have the highest influence on prediction.